Importance and requirements for dental prosthesis order platform services: a survey of dental professionals - Kim, Gyu-Ri; Son, Keunbada; Lee, Du-Hyeong; Kim, So-Yeun; Jin, Myoung-Uk; Lee, Kyu-Bok (Journal of Dental Rehabilitation and Applied Science, 2023)
Purpose: This study aimed to gain better understanding of the importance of dental prosthesis order platform services and to identify the essential elements for their enhancement and wider adoption among dental professionals. Materials and Methods: A survey was conducted to assess the perspectives of dentists, dental technicians, dental hygienists, and dental industry professionals toward dental prosthesis ordering and associated platform services (a total of 53 respondents). The questionnaire was devised after an expert review and assessed for reliability using Cronbach’s alpha coefficient. Factor analysis revealed that 57 factors across five categories accounted for 88.417% of the total variance. The survey was administered through an online questionnaire platform, and data analysis was conducted using a statistical software, employing one-way analysis of variance and Tukey’s honestly significant difference test (α = 0.05). Results: The essential elements identified were accurate information input, effective communication, delivery of distortion-free impressions, convenience in data transmission and storage, development of stable and affordable platform services (P < 0.05). Furthermore, significant differences were observed in the importance of these items based on age, dental profession, and career experience (P < 0.05). Conclusion: The dental prosthesis ordering platform services, the requirements of dental personnel were stability, economic efficiency, and ease of transmitting and storing prosthesis data. The findings can serve as important indicators for the development and improvement of dental prosthesis order platform services. KCI Citation Count: 0